2020
DOI: 10.1002/ptr.6686
|View full text |Cite
|
Sign up to set email alerts
|

Xanthotoxin and umbelliferone attenuate cognitive dysfunction in a streptozotocin‐induced rat model of sporadic Alzheimer's disease: The role of JAK2/STAT3 and Nrf2/HO‐1 signalling pathway modulation

Abstract: The aim of the present study was to assess the neuroprotective effects of xanthotoxin and umbelliferone in streptozotocin (STZ)‐induced cognitive dysfunction in rats. Animals were injected intracerebroventricularly (ICV) with STZ (3 mg/kg) once to induce a sporadic Alzheimer's disease (SAD)‐like condition. Xanthotoxin or umbelliferone (15 mg/kg, i.p.) were administered 5 hr after ICV‐STZ and daily for 20 consecutive days. Xanthotoxin or umbelliferone prevented cognitive deficits in the Morris water maze and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…The neuroprotective effects of xanthotoxin and umbelliferone on streptozotocin (STZ)-induced cognitive dysfunction in rats were evaluated [ 54 ]. Alzheimer’s disease was induced in these animals and both compounds were administrated, proving to prevent cognitive deficits in the Morris water maze and object recognition tests.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of xanthotoxin and umbelliferone on streptozotocin (STZ)-induced cognitive dysfunction in rats were evaluated [ 54 ]. Alzheimer’s disease was induced in these animals and both compounds were administrated, proving to prevent cognitive deficits in the Morris water maze and object recognition tests.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Protectin DX has been verified to inhibit the NF-κB pathway by promoting AMPK, and thus alleviating IL-1β-induced chondrocyte inflammation and inhibiting OA progression in rats ( Piao et al, 2020 ). Interestingly, 8-Methoxypsoralen (also known as Xanthotoxin) has been identified to repress NF-κB activation and inflammatory reactions ( Lee et al, 2017 ; Li et al, 2019 ; Hindam et al, 2020 ). In this study, we found that 8-MOP obviously promoted the expression of SIRT1 and inhibited the expression of NF-κB in the OA model.…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple types of biological and pharmacological activities, the therapeutic effects natural and synthetic coumarins on CNS could be stressed [31,32]. Due to their targeted action on the CNS receptors and enzymes, coumarins could be construed as the potential therapeutics for psychiatric and neurodegenerative disorders (e.g., Alzheimer's and Parkinson's diseases, schizophrenia, anxiety, epilepsy, and depression).…”
Section: Discussionmentioning
confidence: 99%